Biến đổi thủy văn và hiệu quả tài chính công ty nông nghiệp và thực phẩm: Bằng chứng thực nghiệm ở Việt Nam - Đinh Thị Thu, Hồng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study provides empirical evidence of the impact of hydrological change on the financial performance of agricultural and food companies listed on the Vietnam stock market during the period 2003‒2022. Empirical evidence shows that increasing average rainfall, rising sea levels, and decreasing Mekong water levels cause negative impacts on firms’ financial performance. The results also reveal that companies based in the Mekong Delta are more negatively affected by increases in the average rainfall. The water level of the Mekong River during the dry season at Chau Doc station is higher than the average dry season in the period 1979‒1998, creating a beneficial effect to help firms in this region reduce the negative impacts of the low water level. In contrast, the beneficial effect reverses during the flood season.